Influence of pesticide use on flower formation and fertility of some fruit species - Holb, I. J. (International Journal of Horticultural Science, 2008)
This review evaluated previous studies on the effect of pesticide use on flower formation and fertility of some fruit species. The study was divided into two parts. First part of the overview will evaluate the most commonly used fungicides on pollen toxicity and their germination ability under fungicide exposure on different fruit species. Effect of fungicides on fruit set was also critically reviewed. Second part of the study summarised those few studies which determined the effect of some insecticides and acaricides on flower formation and fertility.